The Influence of Pre-Existing Beta-Blockers Use on Survival Outcomes in HER2 Positive Advanced Breast Cancer: Pooled Analysis of Clinical Trial Data - Modi, Natansh D.; Tan, Jin Quan Eugene; Rowland, Andrew; Koczwara, Bogda; Kichenadasse, Ganessan; McKinnon, Ross A.; Wiese, Michael D.; Sorich, Michael J.; Hopkins, Ashley M. (Frontiers in Oncology, 2020)
Beta-blockers (BB) are commonly used to manage cardiovascular disease and may have benefits in controlling complications of anti-HER2 therapies. This study aimed to evaluate the association of pre-existing BB use with survival outcomes in patients initiating anti-HER2 therapy for advanced breast cancer (ABC).Data from clinical trials EMILIA, TH3RESA, MARIANNE, and CLEOPATRA was pooled. Cox proportional analysis was used to assess the association between pre-existing BB use with survival outcomes in patients initiating anti-HER2 therapies.Of the 2,777 patients with HER2 positive ABC, 266 were using a BB at the time of anti-HER2 therapy initiation. BB use was associated with worse overall survival (OS) (adjusted HR= 1.27, 95% CI: 1.04-1.55). Sensitivity analysis in patients with pre-existing cardiovascular disease (CVD) also indicated that BB use was associated with worse OS (1.29, 1.02 -1.63).In large high-quality data, BB use at the time of anti-HER2 therapy initiation for ABC was independently associated with worse OS, regardless of CVD status. The finding is contrary to pre-study hypotheses and findings in other BC subtypes. Future research should aim to gain a deeper understanding of the effects of BBs on specific BC subtypes, cancer types, and cancer treatments.